Antimicrobial Desensitization: A Review of Published Protocols - Daniel B. Chastain; Vanessa Johanna Hutzley; Jay Parekh; Jason Val G. Alegro (MDPI AG, 2019)
Antimicrobial desensitization represents a last-line option for patients with no alternative therapies, where the benefits of this intensive process must outweigh the potential harm from drug exposure. The goal of antimicrobial desensitization procedures is to establish a temporary state of tolerance to drugs that may otherwise cause hypersensitivity reactions. While no universal antimicrobial desensitization protocols exist, this review critically analyzes previously published desensitization protocols. The purpose of this review is to provide a greater insight for clinicians and institutions to ensure desensitization procedures are efficacious while minimizing potential for patient harm. With an increasing rate of antimicrobial resistance and the critical need to preserve antimicrobial agents, desensitization may represent another option in our antimicrobial stewardship toolkit.